Awareness of Forensic Odontology among Dentists in Chitwan - Koirala, Santosh; Jha, Abhishek; Lama, Chhime; Chaulagain, Rajib (Journal of College of Medical Sciences-Nepal, 2025)
Background Through the analysis of dental remnants, forensic odontology contributes significantly to forensic investigations by offering insightful analysis and useful evidence. But dental professionals' awareness and degree of understanding about forensic odontology can have a big impact on how well it works in medico-legal matters. The study was aimed to assess the awareness of forensic odontology among the dentists of Chitwan. Methods A descriptive cross-sectional study was conducted among the dentists of Chitwan from 1st Sept, 2024 to 30th Sept, 2024. This study used self-administered questionnaire to assess the study objectives related to forensic odontology. The self-complete questionnaire collected details on participants’ sociodemographic and primary practice characteristics, exposures and experiences in forensic odontology, awareness of the activities of forensic odontology and their record keeping. The collected data were entered into Microsoft Excel and later transported into SPSS version 16 and then analyzed for descriptive statistics. Results A total of 110 dentists with the mean age of 27.35±5.20 years participated in the study. Majority of the dentists were aware regarding forensic odontology and its role in mass disaster. Approximately 88 (77.3%) of the participants believed that both radiographic examination and eruption patterns were the best ways to estimate dental age. Radiographs, investigation results and patient information were among the various items that were recorded by all the participants. Conclusions The study concluded that all of the dentists were aware about forensic odontology. Lack of practice in maintaining dental records was observed. The records were also not maintained for longer periods. With time, this study focusses, the need of refresher courses for update of knowledge of forensic odontology.